Political Dimensions of the Covid-19 Pandemic: The Risks of Replaced Normalcy - Simeonova, Elena (Research Papers, 2022)
The article presents a critical look at the WHO-announced COVID-19 pandemic, which has been stifling the world for more than a year and clearing the way for the so-called “new normality”. The main goal is to outline the political dimensions of the pandemic and to identify the political and social risks of replaced normalcy. The thesis is that the “new normalcy” is introduced through a coordinated and methodically conducted, at different levels, policy of restrictions, justified by health grounds. This policy generates risks of various kinds, the long-term effects of which threaten the foundations of democratic societies and undermine fundamental civil and political rights and freedoms.